Regulation of transient receptor potential ankyrin 1 by traditional Chinese medicine drugs and their active ingredients - Fang, Yunlong; Lei, Chunxin; Wang, Zihan; Liu, Longxiao; Chen, Yanyu; Chen, Feng; Li, Jingxuan; Tu, Zhikun; Tao, Qingwen; Xu, Yuan (Frontiers in Pharmacology, 2025)
Transient receptor potential ankyrin 1 (TRPA1) has attracted substantial attention for its role as a thermal receptor and regulator of temperature and pain sensing. Notably, Traditional Chinese Medicine (TCM) has demonstrated pharmacological effects through regulation of TRPA1. In this review, we summarize the regulatory effects of TCM drugs and their active ingredients on TRPA1. A total of 31 TCM drugs were identified and categorized into three groups based on their function. Despite the progress in understanding the regulatory effects of TCM drugs and their constituents on TRPA1, further studies are needed to elucidate the molecular mechanisms involved. This review provides a molecular basis for the pharmacological effects of TCM drugs on TRPA1 regulation and offers evidence to support future research in this area.